Coordination structure of various ligands in crosslinked PVA to silver ions for facilitated olefin transport - Kim, JH; Min, BR; Lee, KB; Won, JG; Kang, YS (ROYAL SOC CHEMISTRY, 2002)
The most effective ligand among -OH, -O- and -CHO for facilitated olefin transport by silver ions in room temperature crosslinked poly(vinyl alcohol) membrane has been evaluated.
Keywords: MEMBRANES; SEPARATION; SALTS